Exploring Models of Learning in Networks - Houldsworth, Elizabeth; Alexander, Gillian (Proceedings of the International Conference on Networked Learning, 2004)
In order to explore the concept of learning in networks the paper takes as an example a pan-European e Learning project. We report on a small-scale study involving interviews with six partners and participant observation of the Steering Group meetings. Analysis of the data suggests that there are links with earlier literature on inter-organisational learning networks. We believe our findings are useful not simply for the final stages of this project but also for subsequent attempts to facilitate learning in networks, both by ourselves, and others.